Optimalisasi Edukasi Kesehatan Lingkungan Melalui Penguatan Literasi Dan Bahasa di Dusun V Desa Hulu - Roikestina Silaban; Elvipson Sinaga; Faija Sihombing; Tulus JT Panjaitan; Andi Setia Tafona (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
This research aims to optimize environmental health education by strengthening literacy and language in Dusun V, Hulu Village, Pancur Batu District, Deli Serdang Regency. Conducted from July 15 to July 27, 2024, the study focuses on enhancing public understanding of waste management and environmental health. The methods employed include socializing the processing of organic waste, providing public facilities such as stacked bins and signs prohibiting improper waste disposal, and activating reading parks and literacy programs at PKK. Additional activities include organizing community service projects, sports events, and educational competitions for children. The results indicate that the program was successfully implemented, despite facing technical and coordination challenges. The community responded positively and showed enthusiasm for the initiatives. Challenges included limited expertise in some manufacturing processes and insufficient coordination with relevant stakeholders. Key supporting factors were community support and the facilities provided by residents. Recommendations include improving coordination, reactivating Karang Taruna, and developing MSMEs as part of future local economic empowerment efforts.